2017
DOI: 10.1177/014556131709600817
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Leak during Stapes Surgery: Gushing Leaks and Oozing Leaks, Two Different Phenomena

Abstract: Cerebrospinal fluid (CSF) leak is an uncommon event that can occur during stapes surgery. Such leaks can be classified as gushing leaks (stapes gushers) and oozing leaks. A stapes gusher is a massive flow of CSF through the perforated footplate that fills the middle ear suddenly, while an oozing leak is a slower and less profuse flow. We conducted a retrospective, observational, multicenter study of 38 patients—23 men and 15 women, aged 23 to 71 years (mean: 47)—who had experienced a CSF leak during stapes sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…But on reviewing the CTs after surgery, they could appreciate the enlarged vestibular aquaduct [4]. A retrospective analysis of 38 patients revealed that a watershed closure of ooze should be done intraoperatively [5]. Another retrospective analysis showed that there is no improvement in hearing post operatively managing such cases [4].…”
Section: Discussionmentioning
confidence: 99%
“…But on reviewing the CTs after surgery, they could appreciate the enlarged vestibular aquaduct [4]. A retrospective analysis of 38 patients revealed that a watershed closure of ooze should be done intraoperatively [5]. Another retrospective analysis showed that there is no improvement in hearing post operatively managing such cases [4].…”
Section: Discussionmentioning
confidence: 99%